The Concept of Teaching Russian History at University: from Project to Implementation - N. L. Rosina; M. A. Rosina (Moscow Polytechnic University, 2023)
From September 1, 2023, in accordance with the order of the Ministry of Education and Science and Higher Education of the Russian Federation dated July 19, 2022 No. 662, the number of hours for studying the history of Russia in higher education institutions for students of non-historical specialties will increase. Students of all Russian universities will start studying the updated course of Russian history, expanded in its geographical and chronological framework and covering the events taking place in the country and the world, concerning every citizen of Russia. For teachers, the changes made to the federal state educational standards are detailed in the new concept of teaching the course "History of Russia" approved on February 2, 2023. The concept, representing a social order addressed to education, contains an important ideological message, the development of citizenship and patriotism among students, but does not disclose specific tools to achieve the goals. The article analyzes the psychological, pedagogical and methodological aspects of the most difficult complex problem that will affect the history teacher at the university as the executor of the decisions made. An approach to methodological solutions is determined through clarifying the essence of the phenomena of patriotism, identity, historical consciousness, self-awareness and the psychological mechanisms of their formation in education. The tasks of the teacher as the organizer of the learning situation in learning based on the knowledge of the individual characteristics of students and ways to optimize their personal development on the basis of history are revealed. The article sets the methodological guidelines for moral education in the course of teaching history, due to the requirements of the reform of higher education and modern social challenges. This is all the more important because universities have the right to determine them independently.